Longidorus jagerae sp.n., another longidorid species with globular inclusions in the prerectum (Nematoda: Longidoridae) - J. Heyns; Antoinette Swart (Koedoe: African Protected Area Conservation and Science, 1998)
Longidorus jagerae sp.n. is described from the Western Cape Province, South Africa. It is characterised by the possession of globular inclusions in the prerectum, expanded lip region, posteriorly situated guiding ring, and distinct flanges at the odontophore base. It is compared with the South African species L. fursti and L. mobae, from which it differs among other things in the presence of prerectal inclusions, and with L. pisi and L. latocephalus, from which it can be differentiated mainly by the much longer odon- tostyle, more posteriorly situated guiding ring, and shorter tail.